Interleukin-6, Cortisol, and Brain-Derived Neurotrophic Factor as Biomarkers of the Severity of Traumatic Brain Injury and Its Complications in the Acute and Long-Term Periods: Results of a Prospective Study - S. I. Balan; A. A. Belikova; I. G. Komoltsev; A. V. Timokhova; T. A. Druzhkova; A. E. Talypov; A. B. Guekht; N. V. Gulyaeva (Neuroscience and Behavioral Physiology, 2026)

Preservation of organic traces of life under Martian conditions: Influence of the nature of the smectite in presence - I. Criouet; S. Bernard; E. Balan; F. Baron; A. Buch; F. Skouri-Panet; M. Guillaumet; L. Delbes; L. Remusat; J.-C. Viennet (Icarus, 2026)

Peracetylation transforms natural products beyond mere derivatization - Ambili Sasikumar Athira; Balan Abhijith; M. V. Reshma; Ravi S. Lankalapalli (Natural Product Research, 2025)

Artificial blue light exposure induces anxiety-like behaviour, alters recognition memory and modifies hippocampal morphology in adolescent rats - Iffath Ahmed; Roshan Atif Bashir Eltayeb; Hamdan Iftikhar Siddiqui; Yadukrishnan Moothedath Balan; Baby Chakrapani P. S; Sareesh Naduvil Narayanan (Neuroscience and Behavioral Physiology, 2025)
Background : The constant artificial blue light exposure from electronic gadgets at night raises concerns about its impact on mood and brain functions. This study is designed to evaluate the effect of chronic exposure to artificial blue light from a light-emitting diode (LED) on emotionality, locomotion, novel object recognition memory and hippocampal cytoarchitecture in adolescent rats. Materials and methods : Male albino Wistar rats were exposed to artificial blue light (450 – 495 nm, and 100 Lux) for 14 days from a LED light source. Later, their emotionality, general locomotor behaviours and novel object recognition memory were tested by a computerised behavioural assessment system. After the behavioural assessments animals were euthanized to study the hippocampal cytoarchitecture by Nissl and Golgi-Cox staining. Results : In the open field test, latency to enter the centre zone was significantly increased in blue light exposed animals compared to controls. Total entries to the centre zone and percentage of time spent in the centre zone were slightly reduced in blue light exposed animals. The mean speed of animals in the centre, total zone transitions, and total distance travelled were not different between the two groups. In the elevated plus maze test, entries to the open arm were significantly reduced in blue light exposed animals. Time spent and distance travelled on the open arm were slightly reduced in blue light exposed animals. Entries to the closed arm and time spent in the closed arm were slightly increased but, the distance travelled in the closed arm was significantly reduced in the blue light exposed group. The mean speed of blue light exposed animals on the open arm, closed arm and centre were comparable in the two groups. Rearing duration and total zone transitions were slightly reduced but the total distance travelled was significantly reduced in the light exposed group. Novel object recognition was altered in the light exposed group as indicated by their negative discrimination index values. Hippocampal cornu ammonis-1 (CA1), and cornu ammonis-3 (CA3) regions demonstrated pyknotic cells and CA1 apical dendritic spine density was reduced in blue light exposed rats. Conclusion : Artificial blue light exposure induced anxiety-like behaviours, and significantly altered novel object recognition memory, but only mildly affected the general locomotor behaviours in adolescent rats. Moreover, it induced hippocampal cellular pyknosis and reduced CA1 apical dendritic spine density in blue light exposed adolescent rats.

Artifacts from the methanolic extract of Solanum nigrum Linn - Balan Abhijith; Natakkakath Kaliyathan Raveena; M. V. Reshma; Ravi S. Lankalapalli (Natural Product Research, 2024)

How to identify and forecast severe space weather events - N. Balan; Qing-He Zhang; S. Tulasi Ram; K. Shiokawa; V. Manu; Zan-Yang Xing (Journal of Atmospheric and Solar-Terrestrial Physics, 2024)

Impact of UV radiation on the Raman and infrared spectral signatures of sulfates, phosphates and carbonates: Implications for Mars exploration - C. Royer; S. Bernard; O. Beyssac; E. Balan; O. Forni; M. Gauthier; M. Morand; Y. Garino; P. Rosier (Icarus, 2024)

Effect of IGFBP6 Knockdown on Proteins Regulating Exosome Synthesis and Secretion in MDA-MB-231 Cell Line - A. S. Efimova; I. D. Antipenko; E. A. Evtushenko; P. V. Balan; S. A. Tonevitskaya (Bulletin of Experimental Biology and Medicine, 2023)

Developing an analytical framework for estimating food security indicators in the United Arab Emirates: A review - Khalil A. Ammar; Ahmed M. S. Kheir; Beshir M. Ali; Balan Sundarakani; Ioannis Manikas (Environment, Development and Sustainability, 2023)

An agenda for research and action toward diverse and just futures for life on Earth - C. Wyborn; J. Montana; N. Kalas; S. Clement; F. Davila; N. Knowles; E. Louder; M. Balan; J. Chambers; L. Christel; T. Forsyth; G. Henderson; et al. (Conservation Biology, 2021)
Decades of research and policy interventions on biodiversity have insufficiently addressed the dual issues of biodiversity degradation and social justice. New approaches are therefore needed. We devised a research and action agenda that calls for a collective task of revisiting biodiversity toward the goal of sustaining diverse and just futures for life on Earth. Revisiting biodiversity involves critically reflecting on past and present research, policy, and practice concerning biodiversity to inspire creative thinking about the future. The agenda was developed through a 2‐year dialogue process that involved close to 300 experts from diverse disciplines and locations. This process was informed by social science insights that show biodiversity research and action is underpinned by choices about how problems are conceptualized. Recognizing knowledge, action, and ethics as inseparable, we synthesized a set of principles that help navigate the task of revisiting biodiversity. The agenda articulates 4 thematic areas for future research. First, researchers need to revisit biodiversity narratives by challenging conceptualizations that exclude diversity and entrench the separation of humans, cultures, economies, and societies from nature. Second, researchers should focus on the relationships between the Anthropocene, biodiversity, and culture by considering humanity and biodiversity as tied together in specific contexts. Third, researchers should focus on nature and economies by better accounting for the interacting structures of economic and financial systems as core drivers of biodiversity loss. Finally, researchers should enable transformative biodiversity research and action by reconfiguring relationships between human and nonhuman communities in and through science, policy, and practice. Revisiting biodiversity necessitates a renewed focus on dialogue among biodiversity communities and beyond that critically reflects on the past to channel research and action toward fostering just and diverse futures for human and nonhuman life on Earth.

Microbial biofilm ecology, in silico study of quorum sensing receptor-ligand interactions and biofilm mediated bioremediation - Biji Balan; Amit S. Dhaulaniya; Diksha A. Varma; Kushneet K. Sodhi; Mohit Kumar; Manisha Tiwari; Dileep Kumar Singh (Archives of Microbiology, 2021)

Development of an FTIR based chemometric model for the qualitative and quantitative evaluation of cane sugar as an added sugar adulterant in apple fruit juices - Amit S. Dhaulaniya; Biji Balan; Amit Yadav; Rahul Jamwal; Simon Kelly; Andrew Cannavan; Dileep K. Singh (Food Additives & Contaminants: Part A, 2020)

Cold survival strategies for bacteria, recent advancement and potential industrial applications - Amit S. Dhaulaniya; Biji Balan; Mohit kumar; Pawan K. Agrawal; Dileep Kumar Singh (Archives of Microbiology, 2019)

Enzymatic degradation of polyhydroxyalkanoate using lipase from Bacillus subtilis - P. Kanmani; K. Kumaresan; J. Aravind; S. Karthikeyan; R. Balan (International Journal of Environmental Science and Technology, 2016)

Low-temperature evolution of OH bands in synthetic forsterite, implication for the nature of H defects at high pressure - J. Ingrin; J. Liu; C. Depecker; S. C. Kohn; E. Balan; K. J. Grant (Physics and Chemistry of Minerals, 2013)

Natural Incidence of Leaf Miner Aphanisticus aeneus (Coleoptera: Buprestidae) in Sugarcane Germplasm - P. Mahesh; K. Chandran; T. Manjunatha; S. Balan (Sugar Tech, 2013)

Organic matter governs N and P balance in Danube Delta lakes - E. Durisch-Kaiser; A. Doberer; J. Reutimann; A. Pavel; S. Balan; S. Radan; B. Wehrli (Aquatic Sciences, 2011)

Strategy for Identification of Novel Fungal and Bacterial Glycosyl Hydrolase Hybrid Mixtures that can Efficiently Saccharify Pretreated Lignocellulosic Biomass - Dahai Gao; Shishir P. S. Chundawat; Tongjun Liu; Spencer Hermanson; Krishne Gowda; Phillip Brumm; Bruce E. Dale; Venkatesh Balan (BioEnergy Research, 2010)

Rational selection of structurally diverse natural product scaffolds with favorable ADME properties for drug discovery - D.S Samiulla; V. V. Vaidyanathan; P. C. Arun; G. Balan; M. Blaze; S Bondre; G. Chandrasekhar; A. Gadakh; R. Kumar; G. Kharvi; H.-O. Kim; S. Kumar; et al. (Molecular Diversity, 2005)

Non-Dopaminergic Neurons Expressing Dopamine Synthesis Enzymes: Differentiation and Functional Significance - M. V. Ugryumov; V. I. Mel'nikova; P. V. Ershov; I. S. Balan; A. Kalas (Neuroscience and Behavioral Physiology, 2002)

Effect of semax heptapeptide on rat heart activity during acute hypobaric hypoxia in the early postnatal period - M. V. Maslova; Ya. V. Krushinskaya; A. S. Maklakova; P. V. Balan; Yu. B. Kuznetsov; N. A. Sokolova; I. P. Ashmarin (Bulletin of Experimental Biology and Medicine, 1999)

57 Fe Mössbauer spectroscopy of tektites - S. Rossano; E. Balan; G. Morin; J.-P. Bauer; G. Calas; C. Brouder (Physics and Chemistry of Minerals, 1999)